A Rare Case of Anomalous Insertion of Common Bile Duct and Pancreatic Duct Leading to Acute Pancreatitis in a Child - Nair, Smita; Batra, Sonakshi; Nair, Bindu T (Journal of Society of Surgeons of Nepal, 2024)
The incidence of Acute Pancreatitis is rising among the pediatric population. The most common causes in children are cholelithiasis and choledochal cyst. Anomalies of biliary tract and pancreatic duct are other rare causes of the same. However these anomalies are suspected and detected after repeated episodes of pancreatitis and later in life. We report a case of a 4 year old female child who presented with acute Pancreatitis due to cholelithiasis resulting from a rare anomalous insertion of Common Bile Duct and Pancreatic Duct.